Anthropocentrism and Speciesism in the Context of Environmental Studies. A Synoptic Introduction - Romeo, Maria Vita; Sgarlata, Sara (ETHICS IN PROGRESS, 2020)
Anthropocentrism and Speciesism in the Context of Environmental Studies. A Synoptic Introduction